BENEFITS OF READING LITERATURE ON WRITING IN ENGLISH - Ablakulova Orzigul (Modern American Journals, 2025)
This article examines how reading literature enhances English writing skills through vocabulary enrichment, stylistic development, and grammatical proficiency. Synthesizing existing research, it highlights literature’s role in fostering critical thinking, cultural awareness, and writing motivation. Key findings reveal that consistent literary exposure expands learners' lexical range, models complex syntax, and encourages sophisticated stylistic choices. Additionally, analytical engagement with texts cultivates originality and depth in writing, while cultural narratives improve contextual relevance. The study emphasizes integrating literature into language curricula to maximize writing development and calls for further research on pedagogical strategies and quantitative outcomes.
Keywords: Literature-based language learning, vocabulary acquisition, stylistic development, grammatical proficiency, critical thinking skills, cultural awareness in writing, writing motivation, English writing pedagogy